Scale to Evaluate Employee Experience: Evidence of Validity and Reliability in Regular Basic Education Teachers in the Peruvian Context - Acuña-Hurtado, Nilton (2023)
Research on employee experience is a topic that has been growing in recent decades. This study analyzes the validity and reliability of an employee experience scale in Peruvian teachers. The study had an instrumental design. The sample was comprised of 760 Peruvian teachers between 20 and 71 years old (M = 40.91; SD = 10.05), where men (36.1%) and women (63.9%) participated, recruited through non-probabilistic sampling. A validity and reliability analysis of the employee experience scale confirmed the three original factors (sensory experience, intellectual experience, and emotional experience). The KMO test reaches a high level (0.950 > 0.70), and the Bartlett test reaches a highly significant level (Sig. = 0.000). The scale also showed good internal consistency (α = 0.948 to 0.980; CR = 0.950 to 0.981; AVE = 0.864 to 0.878). Similarly, for the confirmatory factor analysis, a measurement adjustment was performed, obtaining excellent and acceptable fit indices for Model 2 for three factors (CMIN/DF = 4.764; CFI = 0.984; SRMR = 0.024; RMSEA = 0.070). This study provides a useful tool to measure the employee experience in a friendly way, using simple language to be applied to the Peruvian context. This study is considered an important contribution to organizational behavior and human talent management in educational circles.